Assessment of the calcium releasing machinery in oocytes that failed to fertilize after conventional ICSI and assisted oocyte activation. Issue 4 (April 2019) - Ferrer-Buitrago, Minerva; Bonte, Davina; Dhaenens, Lien; Vermorgen, Sanne; Lu, Yuechao; De Sutter, Petra; Heindryckx, Björn
Abstract: Research question: Can oocyte-related activation deficiencies be evaluated in oocytes that failed to fertilize after intracytoplasmic sperm injection (ICSI) combined with assisted oocyte activation (AOA)? Design: Evaluation of the spindle–chromosome complexes and intracellular distribution of inositol trisphosphate type 1 receptors (IP3R1) in in-vitro matured (IVM) and failed-to-fertilize oocytes from patients undergoing AOA. Assessment of the oocyte-related Ca 2+ releasing capacity in response to Ca 2+ ionophores and sperm microinjection in oocytes that failed to fertilize after ICSI or ICSI-AOA. Results: IVM oocytes from patients undergoing conventional ICSI (control) and ICSI-AOA (study group) revealed a similar normalcy of spindle–chromosome complexes and distribution patterns of IP3R1. Failed-to-fertilize oocytes from both groups showed significant differences in proportion of normal or abnormal spindle–chromosome complex conformations. However, migration of IP3R1 was identified in a higher proportion of failed-to-fertilize oocytes after ICSI-AOA than after conventional ICSI. It was further observed that oocytes which failed to fertilize, either after ICSI or ICSI-AOA, mostly retain their capacity to respond to stimuli such as exposure to Ca 2+ ionophores or to sperm microinjection. Conclusions: Evaluation of spindle–chromosome normalcy and distribution of IP3R1 does not help identify the presence of Ca 2+ releasing deficiencies in these oocytes. However, oocyte Ca 2+ analysis adds value in identifying Ca 2+ releasing incapacity of oocytes that failed to fertilize after ICSI or ICSI-AOA. Some patients experiencing fertilization failure after ICSI-AOA present with a suspected activation deficiency downstream of the Ca 2+ machinery, which cannot be overcome by ICSI-AOA based on the use of Ca 2+ ionophores.